2013
DOI: 10.1124/dmd.113.052514
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Investigation of Amyloid-β Hepatobiliary Disposition in Sandwich-Cultured Primary Rat Hepatocytes

Abstract: Failure in amyloid-b (Ab) systemic clearance across the liver has been suggested to play a role in Ab brain accumulation and thus to contribute largely to the pathology of Alzheimer's disease (AD). The purpose of this study was to characterize in vitro the transport mechanisms of Ab 40 across the liver using sandwich-cultured primary rat hepatocytes (SCHs) and to determine its biliary clearance (CL bile ) and biliary excretion index (BEI%). I-Ab 40 biliary excretion was inducible and increased BEI% by 26% afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 51 publications
2
27
0
Order By: Relevance
“…Hence, inhibition of P-gp efflux function by valspodar resulted in more intracellular accumulation of tacrine compared to untreated control. The inhibitory effect of valspodar on P-gp function in SCHs is consistent with our previous report (23). A previous work, however, by Doan and colleagues demonstrated that tacrine is not a P-gp substrate based on permeability screening studies for 93 compounds performed on MDR1-transfected MDCK type II cells (38).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, inhibition of P-gp efflux function by valspodar resulted in more intracellular accumulation of tacrine compared to untreated control. The inhibitory effect of valspodar on P-gp function in SCHs is consistent with our previous report (23). A previous work, however, by Doan and colleagues demonstrated that tacrine is not a P-gp substrate based on permeability screening studies for 93 compounds performed on MDR1-transfected MDCK type II cells (38).…”
Section: Discussionsupporting
confidence: 91%
“…Rats age were around 2-3 months with average body weight between 260 to 340 g. Animals were allowed to easy access for water and standard food and maintained at 22 Isolation of primary rat hepatocytes and preparation of sandwich culture The isolation of hepatocytes from animals' livers were performed as previously described (23). After isolation of hepatocytes by several steps of centrifugation, cells were resuspended in serum-free medium and viability was determined using trypan blue method.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…gp, and MRP2, respectively (Wolf et al, 2008 ± 8%, respectively, which is in the accepted range for hepatocytes with functionally active bile canalicular efflux transporters (Wolf et al, 2008;Mohamed and Kaddoumi, 2013).…”
Section: Biliary Clearance In Rat Schmentioning
confidence: 84%
“…Cryopreserved primary human hepatocytes were revived according to the protocol and seeded in 96-well collagen I-coated plates (BD Gentest) at a density of 3 Â 10 5 cells/ml. Primary rat hepatocytes were prepared with a previously published two-step collagenase perfusion technique with the following modifications: the perfusion buffer and digestion buffer flow rates were set to a constant 17.5 and 15.0 ml/min, respectively; collagenase type II was used instead of type I (Seglen, 1976;Mohamed and Kaddoumi, 2013;Shukla et al, 2013). The fresh primary rat hepatocytes were also seeded in the 96-well collagen I-coated plates at a density of 3 Â 10 5 cells/ml.…”
Section: Methodsmentioning
confidence: 99%